Is implementation of ASAM-based addiction treatment assessments associated with improved 30-day retention and substance use?. (1st September 2021) - Mark, Tami L.; Hinde, Jesse M.; Barnosky, Alan; Joshi, Vandana; Padwa, Howard; Treiman, Katherine
Highlights: ASAM-based assessment implementation was associated with a 9 % increase in 30-day retention in episodes that begin in residential settings. The implementation of ASAM-based assessments was not associated with a change in retention among episodes that began in outpatient settings. There was no association between ASAm-based implementation and successful treatment completion in inpatient or outpatient settings. Abstract: Background: The American Society of Addiction Medicine (ASAM) criteria were developed to provide a systematic, evidence-based, and transparent approach to addiction treatment assessment and level-of-care recommendations. In 2017, California began a Medicaid demonstration that required that providers in participating counties to adopt ASAM-based intake assessments and level-of-care criteria. We hypothesized that ASAM implementation would increase the proportion of patients retained in addiction treatment and successfully completing their treatment plan. Methods: We implemented a comparative interrupted time series analysis with 407, 792 treatment episodes by Medicaid beneficiaries in specialty addiction treatment settings from 2015 to mid-2019. We compared the change in retention rates and successful completion rates in counties that adopted ASAM-based assessments relative to counties that did not adopt ASAM-based assessments and used only clinical judgment for level-of-care decisions. Treatment retention was defined as staying in addiction treatment for at least 30 days. Successful completion of the treatment plan was determined by the patient's clinician. Results: After one year, ASAM implementation was associated with a 9% increase in 30-day retention among treatment episodes that started in a residential setting, but no change in retention among episodes starting in outpatient settings. We found no statistically significant association between ASAM adoption and successful treatment completion. Conclusions: Implementation of ASAM-based assessment may lead to improved retention for individuals who begin treatment in residential treatment, which may be encouraging to the many state Medicaid programs that are adopting ASAM-based criteria. More research is needed to clarify the mechanism by which ASAM leads to improved outcomes and to clarify how to maximize the potential benefits of ASAM, such as through patient-centered implementation.